2017
DOI: 10.1016/j.dmpk.2016.10.410
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of brain tissues of mice chronically exposed to heroin

Abstract: The chronic neurotoxicity of heroin on the nervous system is poorly understood. To address this issue, we comprehensively assessed the alteration of brain metabolomics caused by chronic heroin exposure and the withdrawal of heroin. Male C57BL/6J mice (n = 10) were given heroin (15 μmol/kg, i.p., twice a day) for 12 days while the withdrawal group received saline-treatment instead of heroin for the last two days. The control group received saline. We developed an UPLC-TOF/MS-based metabolomic approach to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Specifically, it has been shown that immune activation can lead to diminished conversion of phenylalanine to tyrosine as evidenced by a higher phenylalanine/tyrosine (P/T) ratio [ 112 ], which has been shown to be present in HIV-infected patients [ 113 ] and potentially contributes to the dopamine deficiency in people living with HIV [ 114 ]. The downregulation of tyrosine in the spinal cord (but not striatum) following repeated morphine treatment supports findings in brain tissue of mice chronically exposed to heroin [ 60 ] and has been shown to allay some of the effects of opioid withdrawal [ 73 ]. In turn, we also report here that morphine leads to a significant upregulation of phenylalanine in the striatum (but not spinal cord) of Tat(−) mice.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Specifically, it has been shown that immune activation can lead to diminished conversion of phenylalanine to tyrosine as evidenced by a higher phenylalanine/tyrosine (P/T) ratio [ 112 ], which has been shown to be present in HIV-infected patients [ 113 ] and potentially contributes to the dopamine deficiency in people living with HIV [ 114 ]. The downregulation of tyrosine in the spinal cord (but not striatum) following repeated morphine treatment supports findings in brain tissue of mice chronically exposed to heroin [ 60 ] and has been shown to allay some of the effects of opioid withdrawal [ 73 ]. In turn, we also report here that morphine leads to a significant upregulation of phenylalanine in the striatum (but not spinal cord) of Tat(−) mice.…”
Section: Discussionsupporting
confidence: 66%
“…In turn, we also report here that morphine leads to a significant upregulation of phenylalanine in the striatum (but not spinal cord) of Tat(−) mice. Similarly, rats self-administrating heroin [ 59 ] and mice undergoing heroin withdrawal [ 60 ] showed elevated levels of phenylalanine in serum. The lack of elevated phenylalanine concentrations in the spinal cord suggests regional differences in its metabolism (similar to tyrosine), which may coincide with regional differences in morphine concentration in the CNS [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, inferring specific health risks associated with the use of synthetic cannabinoids is challenging as limited toxic and pharmacological information is available, and the exact cellular mechanisms underlying memory and learning impairment elicited by substances such as JWH-018 are unclear. Metabolomics, the comprehensive study of global metabolites, is a highly sensitive and powerful tool for systemic toxicological approach 14,15 , and may provide comprehensive information on the dynamic changes induced by JWH-018. Therefore, we aimed to investigate the effects of JWH-018 on the hippocampal metabolome of mice to elucidate the potential mechanism of the impairment in learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they have the potential to become a valuable tool when it comes to the exploration of new mechanisms of toxicity [5,6]. Proteins need a longer period to be either synthetized or degraded [7,8], while metabolomics can give a picture of both long-term and instantaneous reactions of the system induced by the stressor under study [9,10,11].…”
Section: Introductionmentioning
confidence: 99%